FACTORS AFFECTING INTERNATIONAL STUDENT SATISFACTION (ISS) - Jhanghiz Syahrivar (President University, 2016)
This research aimed to determine the Factors Affecting International Student Satisfaction. The populations of this research were international students who enrolled at the Undergraduate Program (S1) of XYZ University. A total of 91 samples were taken by using purposive non-probability sampling technique. Based on the results of previous studies, the researcher took eight (8) independent variables which were assumed to have influences on the dependent variable, International Student Satisfaction. The independent variables being discussed in this research were Education, Social Orientation, Economic Considerations, Safety, Image and Prestige, Technology, Accommodation, and International Student Services. The results showed that eight (8) independent variables simultaneously affect International Student Satisfaction indicated by the F test (simultaneous) with a very high level of significance (0.00a). The research model of this study suggested the level of the coefficient of determination (R Square) of 0768, which means that the research model could explain 76.8% factors affecting International Student Satisfaction at XYZ University. Meanwhile, the remaining 23.2% were explained by factors that were not included in this research. Based on the partial test (t-Test), XYZ University should focus on improving the following factors: Economic Consideration, Safety, Technology, Accommodation, and International Student Services.